1983
DOI: 10.1111/j.1600-065x.1983.tb01080.x
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Elimination of Allogeneic Lymphocytes: Relationship to Established Mechanisms of Immunity and to Lymphocyte Traffic

Abstract: Allogeneic lymphocyte cytotoxicity (ALC) refers to the destruction of lymphocyte beginning within a few hours of intravenous injection into non-sensitized, allogeneic recipients. Usually this has been detected in rats and mice by comparing the localization of 51Cr-labelled lymphocytes in the tissues of allogeneic and syngeneic recipients. In a particular strain combination the existence of ALC is supported by deficient localization of allogeneic lymphocytes in the LN, lungs and blood mononuclear population and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 58 publications
6
37
0
Order By: Relevance
“…Daley and Nakamura (34) have shown that first-generation (F1) animals were able to specifically recognize parental BM cells and that this response seemed to reflect the recognition of some major histocompatibility complex (MHC) genes and some non-MHC genes. Our cytotoxicity results using syngeneic BM targets (F344) and an increased cytotoxicity using MHC-identical but allogeneic BM targets (data not shown) are consistent with the observation that allogeneic BM cells are more rapidly eliminated from the circulation than syngeneic BM cells (35). These data further support the hypothesis that NK cells can recognize MHC and non-MHC genes involved in BM graft rejection.…”
Section: Discussionsupporting
confidence: 86%
“…Daley and Nakamura (34) have shown that first-generation (F1) animals were able to specifically recognize parental BM cells and that this response seemed to reflect the recognition of some major histocompatibility complex (MHC) genes and some non-MHC genes. Our cytotoxicity results using syngeneic BM targets (F344) and an increased cytotoxicity using MHC-identical but allogeneic BM targets (data not shown) are consistent with the observation that allogeneic BM cells are more rapidly eliminated from the circulation than syngeneic BM cells (35). These data further support the hypothesis that NK cells can recognize MHC and non-MHC genes involved in BM graft rejection.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, ALC studies in rats provided ample evidence for stimulatory NK allorecognition both in vivo and in vitro (8,9), and suggested that rat NK cells express a more potent array of activating receptors directed against several distinct target cell allo-MHC determinants encoded within the nonclassical class Ib RT1-C/E/M region (5,10,18,19). We speculated that, like MHC-binding NK receptors in mice and in humans, these rat NK receptors might be functionally associated with DAP12.…”
mentioning
confidence: 90%
“…Con versely, the morphological and biochemical characteristics of HEV could be a conse quence of lymphocyte migration into the node in response to a lymphocyte chemotaxin. Lymphocyte recirculation is independent of surface immunoglobulin [25] and MHC antigens [144] with patterns of recirculation being maintained when cells arc transferred to allogeneic recipients [144], In vitro bind ing of lymphocytes to frozen sections of lymph nodes exhibits the tissue selectivity of recirculation found in vivo [166] and occurs between xenogeneic lymphocytes and lymph nodes [24a]. Woodruff and her colleagues have shown that antibodies raised against a moiety in thoracic duct lymph bind to lym phocytes inhibiting their recirculation in vivo and their binding to HEV in vitro.…”
Section: Margination and Emigration Of Other Classes Of Leucocytesmentioning
confidence: 99%